STRATEGI MARKETING HUBUNGAN MASYARAKAT DAN MEDIA JURNALISTIK DALAM MEMPERTAHANKAN KEPUASAN CUSTOMER K3 MART CABANG KESAWAN KOTA MEDAN - Rana Salsabila; M. Yoserizal Saragih (Jurnal Ilmiah Global Education, 2023)
The rapid growth of the minimarket industry in Medan is contributing to increasingly fierce competition between retail companies, with each company competing to attract consumers with superior offerings and retain existing customers. Promotion is used by businesses to communicate expected messages to audiences and to influence public perception and action. The purpose of this study is to maintain K3mart customer satisfaction with marketing strategies, public relations and journalistic media. This research is a descriptive research using a qualitative approach as an analytical tool. The technique of taking subjects in this study is the Purposive technique. The informants of this researcher came from K3mart employees Jl. Putri Merak Jingga Kesawan and 6 K3mart visitors. Methods of collecting observational data, interviews and documentation. The results showed that Public Relations and Journalism Marketing Strategies through Information helped K3mart customers be happy when they visited Jl. Putri Merak Jingga Kesawan. This is done by sharing information through media, such as by posting content on Instagram, distributing brochures, or putting up banners. By providing good service, friendliness, marketing, public relations, and journalistic tactics through public service are used to make customers happy. Through publication, marketing, public relations, and journalism tactics are used to keep customers happy. K3mart Jl. Putri Merak Jingga Kesawan is done by placing more ads on paper and on social media and informing people about special offers on the products it sells.